Tax Planning, Kebijakan Dividen dan Pengungkapan Enterprise Risk Management terhadap Nilai Perusahaan - Adha Nisa Nurhikmah; Wiwit Irawati (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
The research aims to demonstrate empirically the impact of tax planning, dividend policy, and Enterprise risk management disclosure on firm value. The study involves taking samples of of property and real estate sector companies in the Indonesia stock exchange in 2016-2021. The type of data used in this study is a secondary file of audited annual report published in the Indonesian stock market (bei) from 2016-2021. The sample selection was based on purposive sampling method with the number of companies used as samples is as many as 14 companies with a six-year research period, to obtain as many as 84 samples from the company. Data processing by the Microsoft office excel and statistics e-views 9 by analyzing descriptive statistics, panel data regression model test, classical assumptions, determinations coefficient, panel data regression analysis, statistical f test and statistical. test f, showing tax planning, dividend policy, and Enterprise risk management disclosure, are simultaneously influential to the firm value. Furthermore, the results of the statistical test of Enterprise risk management disclosure are partial to significantly affect firm value, while variable tax planning and dividend policy do not affect firm value.